2004
DOI: 10.1212/01.wnl.0000128044.94294.87
|View full text |Cite
|
Sign up to set email alerts
|

An open study of tacrolimus therapy in Rasmussen encephalitis

Abstract: Seven patients with Rasmussen encephalitis (RE) were treated with the immunosuppressant tacrolimus and followed for a median of 22.4 months. They were compared with 12 historical untreated RE patients (median follow-up 13.9 months). The tacrolimus-treated patients had a superior outcome regarding neurologic function and progression rate of cerebral hemiatrophy but no better seizure outcome. No treated patient, but 7 of 12 control patients, became eligible for hemispherectomy. Tacrolimus did not have any major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 10 publications
(2 reference statements)
1
66
0
2
Order By: Relevance
“…1a) [17][18][19]. Although the rate of progression of atrophic changes is variable, volumetric studies indicate the hemispheric volume loss peaks in the first 8 months of disease [18,20,21]. Interestingly, topographic analysis of brain atrophy showed that the frontal lobe and the insula were preferentially involved by the atrophic process.…”
Section: Introductionmentioning
confidence: 99%
“…1a) [17][18][19]. Although the rate of progression of atrophic changes is variable, volumetric studies indicate the hemispheric volume loss peaks in the first 8 months of disease [18,20,21]. Interestingly, topographic analysis of brain atrophy showed that the frontal lobe and the insula were preferentially involved by the atrophic process.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Based on the prevalence of cytomegalovirus genome in the brains of these patients 8 , we began using ganciclovir, an inhibitor of viral replication as treatment. We have treated a total of eight patients but the three in this report are the only ones treated within three months of onset of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Association has not proved better. Steroids, plasmapheresis, intravenous immunoglobulins, ␣ -interferon and tacrolimus have been used to stop the inflammatory process [4,10,11] . Immunoglobulins seem more eligible as a first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted as a sort of focal autoimmune encephalitis, resulting in a particular epileptic encephalopathy. This hypothesis is based on several facts: (1) clinical resemblance to Russian spring-summer encephalitis of viral origin, which causes epilepsia partialis continua; (2) presence of lymphocyte inflammation and glial nodules in brain biopsy; (3) inconstant finding in serum and cerebrospinal fluid (CSF) of antibodies against subunit 3 of ionotropic glutamate receptor; (4) in some cases, good response to steroids, immunoglobulins and plasmapheresis [2][3][4][5][6][7][8][9][10][11] .We present a patient whose RE apparently began at age 51. We have focused on clinical findings (posterior hemispheric involvement with absence of epilepsia partialis continua), neuroimaging evolution, brain biopsy and good response to intravenous inmunoglobulins.…”
mentioning
confidence: 99%